2010
DOI: 10.1002/polb.22085
|View full text |Cite
|
Sign up to set email alerts
|

Fundamental study of crystallization, orientation, and electrical conductivity of electrospun PET/carbon nanotube nanofibers

Abstract: The morphology, structure, and properties of polyethylene terephthalate (PET)/Carbon Nanotubes (CNT) conductive nanoweb were studied in this article. Nanocomposite nanofibers were obtained through electrospinning of PET solutions in trifluoroacetic acid (TFA)/dichloromethane (DCM) containing different concentrations and types of CNTs. Electrical conductivity measurements on nanofiber mats showed an electrical percolation threshold around 2 wt % multi‐wall carbon nanotubes (MWCNT). The morphological analysis re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
31
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 44 publications
3
31
0
Order By: Relevance
“…is the enthalpy of fusion of perfect crystalline structure of PET at equilibrium thermodynamic melt temperature 0 m T and was taken as 140 J/g [14] .…”
Section: Differential Scanning Calorimetry (Dsc)mentioning
confidence: 99%
See 2 more Smart Citations
“…is the enthalpy of fusion of perfect crystalline structure of PET at equilibrium thermodynamic melt temperature 0 m T and was taken as 140 J/g [14] .…”
Section: Differential Scanning Calorimetry (Dsc)mentioning
confidence: 99%
“…Adding rigid fillers to prepare composite fibers with improved mechanical properties is certainly beneficial for their applications. PET/multi-walled carbon nanotube (MWCNT) composite fibers have been prepared by electrospinning [14,15] . Mazinani et al [14] reported an electrical percolation threshold around 2 wt% MWCNT and significant improvement in mechanical properties through adding MWCNT for random PET fiber mats.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the attention for functionalization has shifted in the recent years towards localized modifications, such as photo-grafting or immobilization of functional groups and polymers on specific reactive sites of the substrate (Ito et al 2007;Vladkova 2010). Another approach reported for polyester fiber functionalization involves electro-spinning in the presence of nano-particles and carbon nano-tubes (Chen et al 2009;Mazinani et al 2010;Xing et al 2011).…”
Section: An Overview Of Polyester Functionalization Techniquesmentioning
confidence: 99%
“…Main objectives of the above forms of polyester functionalization include enhancement of its hydrophilicity (Gouveia et al 2011;Sawada et al 2003), wettability (Bessada et al 2011;Huang et al 2009), dyeability (Hossain et al 2009;Kamel et al 2011), electrical conductivity (Jin et al 2006;Mazinani et al 2010), biodegradability (Xing et al 2011), and addition of new functionalities for e.g. substance entrapment and/or controlled release (Boyd et al 1993;Drobota et al 2010;Kaetsu et al 1999).…”
Section: An Overview Of Polyester Functionalization Techniquesmentioning
confidence: 99%